Autocrine Deactivation of Macrophages in Transgenic Mice Constitutively Overexpressing IL-10 Under Control of the Human CD68 Promoter - Roland Lang; Robert Rutschman; David R. Greaves; Peter J. Murray (2002)
Abstract IL-10 plays an essential role in blocking cytokine production by activated macrophages. To analyze the consequences of enforced expression of IL-10 by macrophages on innate and adaptive immune responses, we generated transgenic mice (macIL-10tg mice) expressing an epitope-tagged IL-10 (Flag-IL-10) under control of the human CD68 promoter. Expression of Flag-IL-10 was constitutive and restricted to macrophages, as shown by sorting splenocyte cell populations and intracellular staining for IL-10. Transgenic macrophages displayed suppressed production of TNF-α and IL-12 upon stimulation with LPS. When macIL-10tg mice were challenged with LPS, serum levels of proinflammatory cytokines were attenuated compared with controls. Infection with Mycobacterium bovis bacille Calmette-Guérin resulted in ∼10-fold-higher bacterial loads than in wild-type mice. Normal T and B cell responses were observed in macIL-10tg mice, suggesting that macrophage-specific overexpression of IL-10 predominantly acts in an autocrine/paracrine manner, resulting in chronically deactivated macrophages that manifest an impaired ability to control pathogens.